2017
DOI: 10.1177/0333102417708203
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and extent of right-to-left shunt on contrast-enhanced transcranial Doppler in Chinese patients with migraine in a multicentre case-control study

Abstract: Background The association between RLS and migraine is still debated. The aim of this study is to investigate the prevalence and grade of RLS in Chinese patients with migraine and to evaluate the relationship between RLS and migraine. Methods A multi-center case-control study of contrast-enhanced transcranial Doppler was conducted in 931 consecutive patients with migraine (240 of 931 had migraine with aura and 691 of 931 were in the migraine without aura group) and 282 were healthy adults. Clinical trial no. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 24 publications
5
27
1
Order By: Relevance
“…Our findings reveal that patients with RLS have higher proportions of NM, suggesting that large hemodynamic changes may significantly relate to migraine symptoms in CHD patients. Although a role for an RLS in triggering migraine remains speculative, several studies worldwide have found a close association between RLS and migraine, particularly in patients with a large RLS and migraine with aura . It may be that substances in the venous circulation, including circulating platelets, chemicals, and 5‐hydroxytryptamine, bypass the filter function of the pulmonary capillary bed by passing through the large cardiac defect and entering the brain, where they trigger a migraine attack …”
Section: Discussionmentioning
confidence: 99%
“…Our findings reveal that patients with RLS have higher proportions of NM, suggesting that large hemodynamic changes may significantly relate to migraine symptoms in CHD patients. Although a role for an RLS in triggering migraine remains speculative, several studies worldwide have found a close association between RLS and migraine, particularly in patients with a large RLS and migraine with aura . It may be that substances in the venous circulation, including circulating platelets, chemicals, and 5‐hydroxytryptamine, bypass the filter function of the pulmonary capillary bed by passing through the large cardiac defect and entering the brain, where they trigger a migraine attack …”
Section: Discussionmentioning
confidence: 99%
“…RLS is an abnormal pathway between the venous and arterial circulations, and includes both intracardiac and extracardiac RLS. Intracardiac RLS are usually related to PFO, which has been described as a "back door to the brain" [17,18]. Hagen et al's autopsy study on 965 normal hearts found that PFO had a prevalence of 27.3% for all age [19].…”
Section: Discussionmentioning
confidence: 99%
“…RLS was diagnosed based on the presence of at least one MB in the 20 s following the initiation of the procedure. We assessed the degree of shunt based on the amount of MBs detected in the Doppler spectrum using unilateral MCA monitoring as follows: mild shunt (1–10 MBs), moderate shunt (10–25 MBs), and large shunt (>25 MBs with shower or curtain patterns) (Wang et al, ) (Figure ). This assessment was performed by an experienced doctor who was blind to the patients' diagnoses.…”
Section: Methodsmentioning
confidence: 99%
“…There is a close association between migraine and right‐to‐left shunt (RLS), usually due to the presence of patent foramen ovale (PFO) (Ailani, ; Wang et al, ). Some studies have reported that the prevalence of RLS in migraine patients with aura (MA) and those without aura (MO) is 2.5‐fold and 1.4‐fold higher, respectively, than that found in healthy control subjects (Schwerzmann et al, ; Wang et al, ). A larger RLS is more common in MA and MO patients than in controls.…”
Section: Introductionmentioning
confidence: 99%